Cell death effect of CD47-agonist peptides on different types of leukemia and in a murine model - Uscanga Palomeque, Ashanti Concepción (2018)
Recently, it has been demonstrated that peptides derived from the C-terminal domain of the TSP1 (4N1K and PKHB1) can activate CD47 and cause caspase-independent and calcium dependent regulated cell death (RCD) selectively in cells of patients with chronic lymphocytic leukemia (CLL). Therefore, the aim of this project was to study the potential of CD47-agonist peptides to induce cell death in different types of leukemia in vitro and in vivo, in an immunocompetent murine model. To achieve this, cell death was evaluated, analyzing phosphatidylserine exposure (Ann-V), cell membrane permeabilization (PI), response to caspase inhibitor (Q-VD-OPh) and calcium chelator (BAPTA) in the different leukemic cell lines, in a murine T cell tumor lymphoblast cell line (L5178Y-R) and in PBMC and murine lymphoid cells. Moreover, the immunogenicity of cell death was evaluated by calreticulin (CTR) exposure, ATP and DAMPs release (HSP70, HSP90, HMGB1, calreticulin). In and in vivo model, tumor volume, survival, cell blood count and tumor histology and immunochemistry (IHC) were assessed, at the same time, administration of a prophylactic antitumor vaccination, and determination of immunologic memory were performed. According to the results PKHB1 is more effective to induce cell death than 4N1K, and induced cell death in each one of the leukemia cell lines tested (MEC-1, Jurkat, CEM, MOLT-4 K562, HL-60 and L5178Y-R). PKHB1 also induced a caspase-independent and calcium-dependent cell death in leukemic cells. Cell death induced by PKHB1 was selective of neoplastic cells and neither affect PBMCs nor cell derived from murine lymphoid organs. Furthermore, ATP and DAMPs release indicate that PKHB1 is able to induce immunogenic cell death. The in vivo, weekly treatment with PKHB1 induces complete regression of L5178Y-R tumors in immunocompetent BALB/c mice, prolonging overall survival. PKHB1 cytotoxicity was also selective in vivo, since none of tissues exposed to this peptide were damaged, and cell blood counts were significantly improved compared to untreated mice. Moreover, the complete regression seems to be related to activation of immune system since the pathological analysis showed PMN and lymphocytes infiltration in the biopsies of treated mice. The IHC revealed the presence of CD4+ and CD8+ lymphocytes. Vaccinated mice showed no tumor growth when re-challenged with L5178Y-R cells. The present study highlights the potential of TSP-mimetic CD47 agonist peptides as therapeutic tools to treat leukemia.